Caffeoylquinic acid profiling: comparative analysis in yerba mate, Indian camphorweed, and stevia extracts with emphasis on the influence of brewing conditions and cold storage in yerba mate infusion - Khaksar, Gholamreza; Chaichana, Nantachaporn; Assatarakul, Kitipong; Sirikantaramas, Supaart (PeerJ, 2024)
Herbal infusions exhibit diverse pharmacological effects, such as antioxidant, anti-inflammatory, anticancer, antihypertensive, and antineurodegenerative activities, which can be attributed to the high content of phenolic compounds (e.g., caffeoylquinic acids (CQAs)). In this study, we used ultraperformance liquid chromatography to determine the content of CQAs in the methanolic extracts of model herbs, namely, yerba mate (Ilex paraguariensis), stevia (Stevia rebaudiana), and Indian camphorweed (Pluchea indica (L.) Less.). The results revealed that yerba mate had the highest total CQA content (108.05 ± 1.12 mg/g of dry weight). Furthermore, we evaluated the effect of brewing conditions and storage at 4 °C under dark and light conditions on the antioxidant property and total phenolic and CQA contents of a yerba mate infusion. The analysis of the yerba mate infusions prepared with different steeping times, dried leaf weights, and water temperatures revealed that the amount of extracted CQAs was maximized (∼175 mg/150 mL) when 6 g of dried leaves were steeped in hot water for 10 min. A total of 10-day refrigerated storage resulted in no significant changes in the antioxidant activity and total phenolic and CQA contents of an infusion kept in a brown container (dark). However, the antioxidant properties and total phenolic and CQA contents were negatively affected when kept in a clear container, suggesting the detrimental effect of light exposure. Our study provides practical recommendations for improving the preparation and storage of herbal infusions, thus catering to the needs of consumers, food scientists, and commercial producers. Moreover, it is the first study of the influence of light exposure on the content of crucial quality attributes within plant-based beverages.
Keywords: Dried leaf weight; Light exposure; Refrigerated storage; Steeping time; Yerba mate; Caffeoylquinic acids (CQAs)